Metabolic state and female fertility in ART cycles: a summary of current advances - Berger, Natascha; Brugger, Katharina; Fluhr, Herbert (Frontiers in Cell and Developmental Biology, 2025)
This mini review explores the evolving landscape of metabolic disturbances and their impact on female reproductive outcomes, with a particular focus on emerging molecular biomarkers and novel metabolic phenotypes. Metabolic health plays a pivotal role in female reproductive function, with well-established endocrine-metabolic disorders, such as polycystic ovary syndrome, obesity, and diabetes mellitus, known to impair fertility. This review explores these conditions, including less commonly studied phenotypes like normal weight obesity, metabolically obese normal weight, and metabolically healthy obesity, which challenge traditional diagnostic frameworks by presenting metabolic risk independent of body mass index. These underrecognized profiles can adversely affect ovarian physiology, endometrial receptivity, and assisted reproductive technology outcomes. The review further highlights potential biomarkers, including bile acids and advanced glycation end-products, as promising diagnostic and therapeutic targets. By integrating insights from metabolic regulation, endocrinology, and reproductive biology, this article emphasizes the need for a more nuanced, individualized approach to fertility assessment and treatment. Understanding these interconnections is vital for advancing personalized medicine, particularly in addressing unexplained infertility and optimizing assisted reproductive technology success.